A proposal for a 360° information system model for private health care organizations. Issue 5 (29th May 2019) - Magalhães, Duarte; Martins, José; Branco, Frederico; Au‐Yong‐Oliveira, Manuel; Gonçalves, Ramiro; Moreira, Fernando
Abstract: At a time when communication, new media, and digitalization are transversal to the whole of society, private health care organizations have the possibility of making their business processes evolve. The objective is thus to seize the benefits associated to the active use of patients' electronic health records (EHRs) as the basis for personalized health care. In order to initially validate the health care sector acceptance of a 360° health care information system (HIS), focused on collecting patients' data to create the necessary knowledge for delivering personalized health care procedures and initiatives, a focus group involving a set of health‐related professionals was performed. Despite recognizing the immense possibilities associated to EHR and its direct incorporation on a 360° HIS, the referred professionals still highlighted their concerns relative to the maintenance of adequate security and privacy levels. With this in mind, a proposal for a 360° HIS model is presented, and its main functional blocks are described with a focus on triggering patient/customer loyalty.